Socioeconomic Analysis of Poverty Issues in Taluka Hala District Matiari, Sindh, Pakistan - Memon, Qurat Ul Ain; jingdong, Luan; Shuangxi, Xiao; Joyo, Mumtaz Ali; Wagan, Shoaib Ahmed; Memon, Irfan Hussain; Wagan, Zohaib Ahmed (Eastern Journal of Economics and Finance, 2016)
The aim of this paper was to identify socioeconomic issues of poverty and what is significance of agricultural sector in household income in Taluka Hala District Matiari Sindh Pakistan. Primary data collection method was used to collect the data. The results revealed that 95 percent of household’s primary source of income was agriculture, 3 percent was engaged in employment and only 2 percent were shopkeeper. On an average income of the respondents was 343519 rupees from rabi crops and 804367 rupees from kharif crops was recorded. Overall average on farm and off farm income was 1396666 rupees was recorded. Poverty profile of respondents was 58.46 percent of the households were under the poverty line using criterion of Rs. 3150 per person per month. The major factors affected for the poverty were high inflation rate, poor employment ratio, low price of agricultural output, low marketing facilities, shortage of water, less literacy ratio, Lack of quality education, poor infra structure, non access on credit facility, very less ratio of women education and employment.